Development of Augmented Reality Media on the Material of Pteridophyta Plant Classification on the Slopes of Mount Gumitir as a Biology Teaching Material for Class X - Rini Fauziah; Evi Hanizar; Hepta Bungsu Agung Jayawardana (Postgraduate, University of Mataram, 2025)
This study aims to develop augmented reality (AR) media on the classification of Pteridophyta for Grade X students. The development followed the 4-D model, including the define, design, develop, and disseminate stages. Visual objects in the form of images and videos of Pteridophyta were obtained from their natural habitat on the slopes of Mount Gumitir and developed into web-based media accessible via smartphones, allowing students to interact directly with the material. Media feasibility validation was conducted by a language expert (90%), a material expert (96%), and a media expert (89%), categorized as highly feasible. A limited trial was conducted in two schools with a total of 88 students in experimental and control classes. Post-test results showed an increase in the average scores of the experimental class (85–86) compared to the control class (40–42). The Mann-Whitney test results (U = 22.50; Z = 7.950; p < 0.001) indicated that the increase was statistically significant. This AR media provides 3D visualizations of real plants, enhancing students' understanding, motivation, and interest in learning. Further development should focus on increasing interactive features and infrastructure support so that this media can be optimally implemented in biology learning.